The era of the “golden workers” and the collective bargaining challenges for the age management in companies - Mariola Serrano Argüeso (Oñati Socio-Legal Series)
The ageing of the population is a fact, and also a worldwide social concern. There are two underlying problems in the business world that must be connected: On one hand, the need for older people to remain in the labour market and, on the other hand, the prejudices that exist in the business world in relation to older people. The plans known as generational diversity plans are essential for keeping older people in the labour market but, taking into account previous experiences, these plans should be developed in the field of the collective bargaining,  preferably in a mandatory manner, which is not currently the case.